RESTENOSIS RISK FACTORS AFTER CORONARY ARTERY STENTING IN OBESE PATIENTS - N. G. Veselovskaya; G. A. Chumakova; V. A. Elykomov; O. V. Gritsenko; A. A. Dashkova; E. V. Trubina; E. V. Kiseleva (Кардиоваскулярная терапия и профилактика)
Aim. To assess the role of epicardial obesity (O) and other metabolic factors in the development of coronary artery (CA) restenosis after CA stenting.Material and methods. The study included 68 men with coronary heart disease (CHD), Functional Class II–III effort angina, aged 38–70 years (mean age 54,4±9,1 years). All participants had Stage I–III O, with the mean body mass index (BMI) of 33,71±3,02 kg/m2. All patients underwent planned angioplasty and stenting of one or two CA. The levels of major and additional metabolic risk factors (leptin, resistin) and proinflammatory markers (interleukin (IL) 6, tumour necrosis factor (TNF) α) were measured. Epicardial obesity was assessed using transthoracic echocardiography (EchoCG) in B-mode, with the linear measurement of epicardial adipose tissue (EAT) behind the right ventriculum.Results. During the first year after CA stenting, 28% of the patients developed in-stent restenosis. The most important determinants of the restenosis risk were IL-6, adiponectin, EAT thickness, and leptin. In patients with restenosis, the mean EAT thickness value (8 (5–10) mm) was almost twice as large as in restenosis-free patients (4,3 (3–6) mm; p<0,001). In participants with EAT thickness >3 mm, 38% had CA restenosis; for patients with EAT thickness of >5 mm and >7 mm, the respective figures were 52% and 66%. The multivariate analysis results suggested that the combination of epicardial O and baseline elevation of IL-6 and leptin significantly increases the risk of restenosis (odds ratio 18,9; 95% confidence interval 8–145; p<0,001).Conclusion. Increased EAT thickness at EchoCG was linked to the risk of restenosis. The combination of epicardial O and baseline elevation of pro-inflammatory markers and markers of neurohumoral activation of visceral fat tissue has a significant impact on the risk of myocardial revascularisation complications.